Association of screen exposure/sedentary behavior and precocious puberty/early puberty - Wu, Xinyu; Wang, Lingmei; Xue, Peng; Tang, Jingyi; Wang, Haodong; Kong, Huijun; Lin, Cuilan; Chang, Bo; Liu, Shijian (Frontiers in Pediatrics, 2024)
Background ：In recent years, with the development of society, children's daily exposure to screen time has gradually increased. Screen exposure and sedentary behavior have brought a host of harms to children's lives. The aim of this study was to explore the effects of screen exposure and sedentary behavior on precocious puberty and early development. Methods： This is a cross-sectional study in the school-based population. A total of 3,560 children were recruited from Qufu City, Shandong province using multistage stratified cluster random sampling. All study subjects had a physical examination by professional pediatricians in October 2019, and were investigated with health questionnaires. Precocious puberty is defined as development of secondary sexual signs in boys before 9 years or in girls before 8 years. Screen time was calculated as the average of screen time on weekdays and weekend days, and sedentary time was calculated as the average of sedentary time on weekdays and weekend days. After adjusting for potential confounders, logistic regression was used to examine the association between screen exposure and sedentary behavior and early puberty and precocious puberty. Results： Sedentary time was a risk factor for precocious puberty and early development (OR = 1.428, 95%CI= 1.087-1.876) in girls without adjustment. No significant association was found between screen exposure and early puberty and early development both in girls and boys. Conclusions ：Excessive sedentary behavior was associated with an increased risk of early puberty, especially in girls, while there was no significant association between screen exposure and early puberty and early development. In addition, further longitudinal investigations are needed to determine the causal relationship between screen exposure, sedentary behavior and precocious puberty.